I think that's going to be really hard, because I looked for it @ Wolphram alpha:
solve ((A/B)-1)*((A^2/C^2)-1)=2(A/C)((D*E) ;/F) for A - Wolfram|Alpha
Hi, I'm new to this site and I hope you guys can help. I'm not actually pre university but an engineer, yet I'm having some problems rearranging an equation and was hoping someone could help. The equation is as follow:
((A/B)-1)*(((A/C)^2)-1)=2*(A/C)*((D*E)/F)
and the equation needs rearranging to find A. Can anyone help?
Thanks
I think that's going to be really hard, because I looked for it @ Wolphram alpha:
solve ((A/B)-1)*((A^2/C^2)-1)=2(A/C)((D*E) ;/F) for A - Wolfram|Alpha
I start first by distrubuting the exponents to get:
(B/A)*(C^2/A^2) = (2ADE)/(CF)
Next, combine like bases and simplify:
(BC^2)/(A^3) = (2ADE)/(CF)
Multiply both sides by A^3 to get:
BC^2 = (2A^4DE)/(CF)
Multiply both sides by (CF) to get:
BC^3F = 2A^4DE
Divide both sides by 2DE to get:
(BC^3F)/(2DE) = A^4
Take the fourth root of each side to get:
A = fourth_root[(BC^3F)/(2DE)]